Analisis Dampak Pertapaan Ratu Kalinyamat terhadap Kondisi Sosial dan Ekologis Masyarakat Dukuh Sonder Era Modern - Saputra, Muhammad Teguh; Nadira, Sylvia Putri (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
This research is important with the following considerations: (1) There are still few studies that raise similar themes in terms of use value (2) Cultural heritage sites such as the Kalimat hermitage need to be maintained (3) Seeing the Kalimat hermitage from the side of its function is important in the modern era (4) Value The noble community began to be eroded by the current of modernization, so it was important to treat the site like the site that the researchers adopted. This study aims to determine the pragmatic side of the Ratu Kalinyamat Hermitage on the life of the Dukuh Sonder community around the Ratu Kalinyamat Hermitage. This goal can be determined by analyzing the impact of the hermitage on the social and ecological conditions of the people of Dukuh Sonder. Qualitative descriptive is the method that the researcher chooses in this research to explain complex social and natural events. As a test of validity, source triangulation is the method chosen. The results of this study indicate, from a social perspective, hermitage has an influence in forming consensus on the Sonder community and from an ecological perspective it has no effect on the Sonder community, it is the culture of the Sonder community that influences the Hermitage's environment so that it can be managed properly. So it can be concluded, the Hermitage of Ratu Kalinyamat is not eroded by modern currents because of the pragmatic and cultural dimensions inherent in society.